2010
DOI: 10.1007/s11482-010-9134-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diseconomies of Transportation and Public Safety Problems in the Measurement of Urban Quality of Life

Abstract: Quality of Life has become an issue of urban research due to a greater awareness of its contribution when identifying areas for intervention and when monitoring urban planning policies. This case study from Costa Rica refers to the role of diseconomies of transportation and public safety problems in the measurement of urban quality of life. Theoretically, urban diseconomies, or negative externalities, are the result of rises in average total costs over time as production increases and of the use of certain fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Many studies have attempted to define QoL and to measure it from an analytical perspective. Some authors have suggested that QoL studies are most suited to the study of urban life, due to the contradictions characterizing urban environments (Pichardo-Muñiz 2011 ). The urban railway transit space is a common public space shared by different users, and thus is a suitable place to conduct QoL research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have attempted to define QoL and to measure it from an analytical perspective. Some authors have suggested that QoL studies are most suited to the study of urban life, due to the contradictions characterizing urban environments (Pichardo-Muñiz 2011 ). The urban railway transit space is a common public space shared by different users, and thus is a suitable place to conduct QoL research.…”
Section: Discussionmentioning
confidence: 99%
“…When low level needs are fulfilled, people begin to focus on their high level needs, and these higher level needs will alter users’ behavior for both objective and subjective reasons. The objective perspective focuses on the external conditions contributing to QoL, whereas the subjective perspective is based on people’s internal judgment as it relates to QoL (Pichardo-Muñiz 2011 ). For instance, people focus on their high level needs in a more developed URT space.…”
Section: Quality Urt Experience Pyramidmentioning
confidence: 99%